Benefits Associated With Experiential and Material Purchases May Depend on Culture. Issue 5 (July 2020) - Razavi, Pooya; Shaban-Azad, Hadi; Chai, Wen Jia; Zhang, Jia Wei; Nguyen, Ngoc-Han; Howell, Ryan T.
Spending money on experiences, compared to materials, is often associated with more happiness. This experiential advantage, however, is developed based on samples from Western cultures. To investigate the boundaries of this effect, we studied participants from three divergent cultures (Iran, Malaysia, and the United States; N = 1, 718) and examined the benefits associated with different purchase types across material–experiential and solitary–social dimensions. Results indicated a cross-culturally robust experiential advantage in terms of affiliative outcomes (i.e., positive other-focused emotions and relational enhancement), even when we accounted for the sociality of the purchases. However, the results were less consistent with the experiential advantage in terms of happiness and self-focused outcomes (i.e., self-focused emotions and self-elevation). Interestingly, experiential-solitary purchases were associated with stronger self-focused benefits among Iranians. We discuss possible explanations for this effect and offer recommendations for future research. Data and analysis code are publicly available athttps://osf.io/n39gj/